Implementing Reading to Learn (R2L) Pedagogy to Help Indonesian Junior High School Students Generate News Report Text - Yulianeta Yulianeta (Master Program in Linguistics, Diponegoro University, 2022)
The Reading to Learn (R2L) pedagogy, which requires preparing for reading, detailed reading, joint construction, and independent construction steps, was invented in Australia to assist Australian indigenous secondary school students in reading texts and finding useful information inside the texts. This one group pre-test and post-test design was aimed at unfolding the effectiveness of R2L pedagogy in helping the students in constructing well-structured news report texts. A total of 51 ninth-grade students from a junior high school, Bandung, Indonesia participated in the research. The students received the R2L pedagogy in four meetings within a month, excluding the pre-test and post-test.